2017
DOI: 10.1016/j.neo.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Stromal PDGFR-α Activation Enhances Matrix Stiffness, Impedes Mammary Ductal Development, and Accelerates Tumor Growth

Abstract: The extracellular matrix (ECM) is critical for mammary ductal development and differentiation, but how mammary fibroblasts regulate ECM remodeling remains to be elucidated. Herein, we used a mouse genetic model to activate platelet derived growth factor receptor-alpha (PDGFRα) specifically in the stroma. Hyperactivation of PDGFRα in the mammary stroma severely hindered pubertal mammary ductal morphogenesis, but did not interrupt the lobuloalveolar differentiation program. Increased stromal PDGFRα signaling ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 64 publications
5
44
0
Order By: Relevance
“…CAFs are most commonly identified by their expression of fibroblast activation protein (FAP) and alpha smooth muscle actin (∂-SMA), however, additional markers including platelet derived growth factor receptor b (PDGFRB), fibroblast specific protein (FSP) and vimentin (VIM), all of whose expression in tumor stroma have, like ∂-SMA, been linked to poor outcome of many cancers, can also be expressed in CAFs (Jacob et al, 2012 ; Folgueira et al, 2013 ; Paulsson and Micke, 2014 ; Han et al, 2015 ; Peiris-Pagès et al, 2015 ; Corvigno et al, 2016 ; Gascard and Tlsty, 2016 ; Kuzet and Gaggioli, 2016 ; Hammer et al, 2017 ; Tao et al, 2017 ; von Ahrens et al, 2017 ). The roles of CAFs as promoters of tumor initiation, progression, epithelial to mesenchymal transition, stemness, tumor invasion, angiogenesis, metastasis and drug resistance are well established (Kalluri and Zeisberg, 2006 ; Shekhar et al, 2007 ; Straussman et al, 2012 ) Experimentally, CAFs exhibit activity in all Hallmarks of Cancer categories (Salo et al, 2014 ; Tommelein et al, 2015 ; Attieh and Vignjevic, 2016 ; Mezawa and Orimo, 2016 ).…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…CAFs are most commonly identified by their expression of fibroblast activation protein (FAP) and alpha smooth muscle actin (∂-SMA), however, additional markers including platelet derived growth factor receptor b (PDGFRB), fibroblast specific protein (FSP) and vimentin (VIM), all of whose expression in tumor stroma have, like ∂-SMA, been linked to poor outcome of many cancers, can also be expressed in CAFs (Jacob et al, 2012 ; Folgueira et al, 2013 ; Paulsson and Micke, 2014 ; Han et al, 2015 ; Peiris-Pagès et al, 2015 ; Corvigno et al, 2016 ; Gascard and Tlsty, 2016 ; Kuzet and Gaggioli, 2016 ; Hammer et al, 2017 ; Tao et al, 2017 ; von Ahrens et al, 2017 ). The roles of CAFs as promoters of tumor initiation, progression, epithelial to mesenchymal transition, stemness, tumor invasion, angiogenesis, metastasis and drug resistance are well established (Kalluri and Zeisberg, 2006 ; Shekhar et al, 2007 ; Straussman et al, 2012 ) Experimentally, CAFs exhibit activity in all Hallmarks of Cancer categories (Salo et al, 2014 ; Tommelein et al, 2015 ; Attieh and Vignjevic, 2016 ; Mezawa and Orimo, 2016 ).…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Fibroblasts are major contributors to the distinct desmoplastic reaction in PDAC that alter the architecture and mechanics of the ECM ( Provenzano et al, 2012 ; Stylianopoulos et al, 2013 ). We designed an in vitro assay using a microfluidic device ( Hammer et al, 2017 ) to test whether PTEN in tumor fibroblasts affects the hydraulic permeability (K), which is a characteristic of the ECM that relates interstitial fluid velocity to the fluid pressure gradient ( Wiig & Swartz, 2012 ) ( Fig S6A–D ). This in vitro assay demonstrated that human pancreatic tumor fibroblasts with PTEN knockdown had increased resistance to flow (i.e., decreased K) compared with control ( Fig 6D and E ).…”
Section: Resultsmentioning
confidence: 99%
“…For example, patterning of collagen fibers in the mammary gland stroma regulates the orientation of TEBs during branching morphogenesis (Brownfield et al, 2013). Recent publications reported important role of fibroblasts in regulation of ECM composition, abundance and organization, and thereby in regulation of mammary epithelial branching morphogenesis (Feinberg et al, 2018;Hammer et al, 2017;Koledova et al, 2016;Morsing et al, 2016;Peuhu et al, 2017). We found that FGF signaling in fibroblasts regulates expression of several ECM genes, including collagens.…”
Section: Discussionmentioning
confidence: 66%
“…Stromal fibroblasts are important regulators of mammary epithelial morphogenesis (Hammer et al, 2017;Koledova et al, 2016;Morsing et al, 2016;Peuhu et al, 2017). Therefore, we investigated the role of FGF2 signaling in fibroblasts in epithelial branching morphogenesis using 3D cultures of mammary organoids alone, fibroblasts alone, and co-cultures of organoids with fibroblasts.…”
Section: Fgf2 Signaling In Fibroblasts Enhances Fibroblast-induced Brmentioning
confidence: 99%
See 1 more Smart Citation